Combining studies with family: Being a student and a parent at the same time - Álvarez Moral, Diego; Guerra Maldonado, Catalina; Tapia Sepúlveda, Karen; Varas González, Gonzalo (Revista de Sociología, 2020)
This article addresses the strategies adopted by university students who are also parents as they combine academic and family activities, exploring the repercussions of these strategies at a subjective level in terms of mental health and perceptions of their performance in the two roles. Semi-structured interviews were applied to students who are parents at the five University of Chile campuses. Results were interpreted using discourse analysis and reveal long, exhausting, and varied daily routines involving considerable personal demand and reliance on support networks. These strategies were found to have negative consequences in terms of mental health and to generate non-traditional perceptions of youth and parenthood. The study proposes foundations for the promotion of university spaces and guidelines that are more sympathetic to students who are also parents.